Biotechnological Conversion of Grape Pomace to Poly(3-hydroxybutyrate) by Moderately Thermophilic Bacterium Tepidimonas taiwanensis - Kourilova, Xenie; Pernicova, Iva; Vidlakova, Michaela; Krejcirik, Roman; Mrazova, Katerina; Hrubanova, Kamila; Krzyzanek, Vladislav; Nebesarova, Jana; Obruca, Stanislav (Bioengineering (Basel, Switzerland), 2021)
Polyhydroxyalkanoates (PHA) are microbial polyesters that have recently come to the forefront of interest due to their biodegradability and production from renewable sources. A potential increase in competitiveness of PHA production process comes with a combination of the use of thermophilic bacteria with the mutual use of waste substrates. In this work, the thermophilic bacterium Tepidimonas taiwanensis LMG 22826 was identified as a promising PHA producer. The ability to produce PHA in T. taiwanensis was studied both on genotype and phenotype levels. The gene encoding the Class I PHA synthase, a crucial enzyme in PHA synthesis, was detected both by genome database search and by PCR. The microbial culture of T. taiwanensis was capable of efficient utilization of glucose and fructose. When cultivated on glucose as the only carbon source at 50 °C, the PHA titers reached up to 3.55 g/L, and PHA content in cell dry mass was 65%. The preference of fructose and glucose opens the possibility to employ T. taiwanensis for PHA production on various food wastes rich in these abundant sugars. In this work, PHA production on grape pomace extracts was successfully tested.
Keywords: grape pomace; polyhydroxyalkanoates; Tepidimonas taiwanensis; thermophiles